PHYSIOTHERAPY AND HEALTHFUL AGING: QUALITATIVE STUDY IN THE PRIMARY ATTENTION OF THE PUBLIC SYSTEM OF HEALTH (Fiep Bulletin - online, 2014)
To consider questions on the aging process of the people is a determinant factor for the formulators of the public polices being this a priority in the national agenda, but to think of public polices for the elderly not only means to make interventions when they are already in an advanced age. This research is related to promoting a healthful aging process. The objective is the application of a Postural Education Program with women ranging from 35 to 45 years old, as well as the understanding of their perceptions on their own body and aging. This is an intervention research which derived from the study of two cases. The results demonstrated that the participants learned how to have a better relation with their own body, showed signs of improvement in the pains as well as in the quality of both the static and in movement posture. It also revealed a concern about the collective expressing that this work could help a greater number of people. This experience indicates that the performance of the physiotherapist at the UBS can contribute to the principle of completeness of the prevention actions and health promotion on the Basic Attention of the SUS.